Mobile Behavior of Mosquito Larvae Culex Sp. After Administration of Biolarvacide Basic Leaves (Ocimum Sanctum L.) with Pineapple Skin Bioethanol - Ulya Amirah; Supriatno Supriatno; Devi Syafrianti; Safrida Safrida; Iswadi Iswadi (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2023)
ABSTRACTMosquitoes Culex sp. type of insect that is known as a vector for transmitting dangerous diseases, so it is necessary to controll iit so that it does not become a disease outbreak by utilizing plants such as basil leaves which can be an alternative insecticide. Pineapple peel is waste that can be used as bioethanol to be used as an organic solvent because it is polar. The study is aimed to determiine the movement behavior of Culex sp. mosquito larvae. after exposure to basil leaf extract before death. With 6 treatmnts and 4 repications, the research methodology utilized was a completely randomized design (CRD). As a treatment, water was used as a negative control (P0), basil leaf extract at concentrations of 1000 ppm, 1500 ppm, 2000 ppm, and 2500 ppm was used as a positive control (P4), and abate was used as a therapy at 100 ppm (P5). The Culex sp. mosquito larvae's behavior after being exposed to basil leaf extract was measured using the parameters. ANOVA was used to examine the data. The results of ANOVA on movement behavior of the larvae showed Fcount = 43.71 Ftable = 4.25. at the test level α = 0.01. This study concludes that Culex sp mosquito larvae that have been exposed to basil leaf extract show changes in moving behavior from previously active to inactive and finally die.Keywords: Behavior, Basil, Culex sp.ABSTRAK Nyamuk Culex sp. ialah jenis serangga yang dikenal sebagai vektor penular penyakit berbahaya, sehingga perlu pengendali agar tidak menjadi wabah penyakit dengan memanfaatkan tumbuhan seperti daun kemangi yang dapat menjadi alternatif insektisida. Kulit nanas merupakan limbah yang dapat dimanfaatkan sebagai bioetanol untuk dijadikan pelarut organik karena bersifat polar. Tujuan penelitian ini ialah untuk melihat tingkah laku bergerak larva nyamuk Culex sp. setelah terpapar ekstrak daun kemangi sebelum kematian. Rancangan penelitian yang dipakai ialah Rancangan Acak Lengkap (RAL) menggunakan 6 perlakuan dan 4 kali ulangan. Perlakuan yang diberikan yaitu air (P0) sebagai kontrol negatif, konsentrasi ekstrak daun kemangi 1000 ppm (P1), 1500 ppm (P2), 2000 ppm (P3), 2500 ppm (P4) dan abate 100 ppm (P5) sebagai kontrol positif. Parameter yang diamati adalah tingkah laku larva nyamuk Culex sp. setelah terpapar ekstrak daun kemangi. Data dianalisis menggunakan ANAVA. Hasil ANAVA terhadap tingkah laku bergerak larva menunjukkan Fhitung = 43,71 Ftabel = 4,25. pada taraf uji α = 0,01. Simpulan dari penelitian ini ialah larva nyamuk Culex sp yang telah terpapar ekstrak daun kemangi menunjukkan perubahan tingkah laku bergerak yang sebelumnya aktif bergerak menjadi tidak aktif dan akhirnya mengalami kematian.Kata Kunci: Tingkah laku, Kemangi, Culex sp.